2021
DOI: 10.3389/fphar.2021.646307
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Postconditioning Attenuates Hepatic Ischemia-Reperfusion Injury by Limiting HMGB1/TLR4/NF-κB Pathway via Modulating microRNA-142 in vivo and in vitro

Abstract: Preconditioning of sevoflurane (Sevo) has been demonstrated to protect the liver from ischemia/reperfusion (I/R) injury. However, it is unknown whether it has hepatoprotective when given at the onset of reperfusion (postconditioning), a protocol with more clinical impact. The present study aimed to explore the hepatoprotective effects of Sevo postconditioning against hepatic IR injury in vivo and in vitro and the possible mechanisms. Using a mouse model of hepatic I/R, Sevo postconditioning significantly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 59 publications
2
24
0
1
Order By: Relevance
“…TLR-4 signaling promotes MyD88-dependent pathways, which leads to the activation of nuclear factor kappa B (NF-κB), which is essential for production of proinflammatory cytokines 8 , 9 . Induction of the signaling pathway of NF-κB is one of the main mediators of inflammation and defines the development and progression of hepatic IRI 10 , 11 . As the most studied tissue-damage detector, the NLR family pyrin domain-containing 3 (NLRP3) inflammasome is composed of NLRP3, apoptosis-associated speck-like protein (ASC) and caspase-1, which is prominent in initiating and propagating the inflammatory responses 12 .…”
Section: Introductionmentioning
confidence: 99%
“…TLR-4 signaling promotes MyD88-dependent pathways, which leads to the activation of nuclear factor kappa B (NF-κB), which is essential for production of proinflammatory cytokines 8 , 9 . Induction of the signaling pathway of NF-κB is one of the main mediators of inflammation and defines the development and progression of hepatic IRI 10 , 11 . As the most studied tissue-damage detector, the NLR family pyrin domain-containing 3 (NLRP3) inflammasome is composed of NLRP3, apoptosis-associated speck-like protein (ASC) and caspase-1, which is prominent in initiating and propagating the inflammatory responses 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In mouse model of IRI, Xu et al . showed that sevoflurane can inhibit the expression of high mobility group box 1 (HMGB1) to up-regulate microRNA (miR)-142 [ 41 ]. Adoptive HSCs confer protection against IRI by inducing newborn inducible regulatory T cells (iTregs) and increasing the stability of natural regulatory T cells (nTregs) [ 42 ].…”
Section: Hepatic Microenvironmentmentioning
confidence: 99%
“…Sevoflurane demonstrates protective effects in the heart, liver, lung, and brain (Toller et al, 1999;Tong et al, 2014;Wang et al, 2019;Xu et al, 2021). They are also known to increase the survival of sepsis model mice.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to decrease the size of infarct areas in the ischaemic stroke model and cardiac infarction models (Toller, Kersten, Pagel, Hettrick, & Warltier, 1999; Tong et al, 2014). Sevoflurane demonstrates protective effects in the heart, liver, lung, and brain (Toller et al, 1999; Tong et al, 2014; Wang et al, 2019; Xu et al, 2021). They are also known to increase the survival of sepsis model mice.…”
Section: Introductionmentioning
confidence: 99%